Chaksu Bunga: Augmented Reality Media to Enhance Fourth-Grade Students’ Learning Interest - I Putu Eka Indrawan; Ni Nyoman Parmithi; Ni Luh Putu Yesy Anggreni; I Wayan Eka Mahendra (Universitas Pendidikan Ganesha, 2025)
This study is motivated by the limited ability of teachers to integrate Augmented Reality (AR) technology with local spiritual values, which results in low student participation and the suboptimal internalization of character values through culturally based visual learning. Existing learning media tend to be monotonous and one-directional, failing to stimulate students’ learning interest and appreciation for local culture. This research aims to develop and evaluate the effectiveness of the Chaksu Bunga AR-based learning media, which is grounded in the philosophy of Chaksu Indriya. The media not only presents three-dimensional visualizations of flowers but also incorporates Hindu local values in an interactive and visual format. The study employs a Research and Development (R&D) approach using the ADDIE model and involves 46 students as trial subjects. Data were collected through observations, validation questionnaires, and learning outcome tests. Instruments included expert validation sheets, student response questionnaires, and achievement tests. The data were analyzed using both descriptive quantitative and qualitative methods. The findings indicate that the Chaksu Bunga AR media is valid, practical, and effective in enhancing students’ understanding of science concepts and fostering the internalization of character values through a spiritually and aesthetically grounded cultural approach. The study implies the importance of developing contextual learning media that integrates technology and local wisdom as part of 21st-century educational transformation.